Determinants of Entrepreneurial Behavior - Nabillah, Nida Anisatun; Rusdarti, Rusdarti; Setyadhrama, Andryan (Universitas Negeri Semarang, 2024)
Entrepreneurial behavior is a real action that is ideally carried out by an entrepreneur because of the stimulus or stimulation in running a business. This research aims to determine the influence of social support, self-efficacy, and entrepreneurial motivation on entrepreneurial interest through entrepreneurial interest. The population in this study were 143 students from the Faculty of Economics and Business, Universitas Negeri Semarang who were self-employed or self-employed. This study used total sampling. The data collection technique in this research uses a questionnaire whose validity and reliability have been tested. Meanwhile, the data analysis techniques used include descriptive analysis, path analysis, and Sobel test. The research results show (1) social support, self-efficacy and entrepreneurial motivation influence entrepreneurial interest; (2) social support, self-efficacy and entrepreneurial motivation influence entrepreneurial behavior through entrepreneurial interest; (3) interest in entrepreneurship influences entrepreneurial behavior. It is hoped that this research can contribute to the development of science and test the theory of planned behavior related to entrepreneurial behavior as a basis for increasing student entrepreneurship.